Civilisational bifurcation of the great Middle East - Mamedov, Agamali K. (Journal of the Belarusian State University. Sociology, 2021)
The main attention of the work is paid to the analysis of possible options for the civilisational development of the countries of the Middle East. Various proposals, concepts of researchers, thinkers are presented, but the main emphasis is on considering the consequences of the introduction of certain alternatives, including the experience of past centuries, as well as the possibility of using alternative solutions in modern conditions. The article discusses the idea of the uniqueness of the historical and civilisational development of the Middle East. The parameters of the search for options for social development are revealed.
Keywords: bifurcation; globalisation; ideology; value orientations; national identity; global civilisation; Islamic civilisation space; Islamisation of modernity; civilisational shifts